Inside pages a content analysis of stories on ancestral domain/land of Cordillera indigenous peoples by the Baguio press - Anga-angan, Melanie; Atuban, Wendy; Dacuag, Lovedyn (2010)
This study is a content analysis of stories published by five Baguio newspapers- Baguio Midland Courier, Baguio Reporter, Cordillera Today, Northern Dispatch Weekly and Pulso ng Bayan - about the ancestral domain/land of the indigenous peoples in the Cordillera. This research examined 85 articles(news stories, opinions/columns, features, and investigative reports) published from April to July 2009- April being month when the Cordillera region was founded and July being the month when the Cordillera Administrative Region was established. The study analyzed and described how the five Baguio newspapers presented ancestral domain/land issues of the IPs in the Cordillera. The research found that the five newspapers had been objective in their reportage of the AD/L issues of the indigenous peoples by not giving a more comprehensive and extensive reporting of the issues. Most of the stories went unexplained- the indigenous peoples are underrepresented in the stories; only advocacy newspapers managed to report extensively on the issue. The research used Gerbner's concepts of "all news are views", "no fundamentally non-apolitical, non-ideological, non partisan news gathering and reporting system", and "public message system" -- Author's abstract.